De indio a serrano: nociones de raza y geografía en el Perú (siglos XVIII-XXI) - Méndez Gastelumendi, Cecilia (2011)
In Peru the terms Indian and serrano (technically, a person from the hills or the mountains) are used as synonyms, and are frequently considered insults. But it wasn’t always like that. In colonial times the term Indian was not associated with any geographical region in particular. Indians could be found anyplace: on the coast, in the foothills or in the mountains. However, at some moment toward the end of the eighteenth century, and most of all during the course of the nineteenth century, the term Indian came to be intrinsically associated with the mountains, and the word serrano acquired a derogatory connotation. Based on literary, historical and visual sources this article aims to describe the process by which the concept of Indian came to be closely associated with serrano, and how the adjective serrano became a substantive and, finally, how that term ended up in Peru as an insult.